1987
DOI: 10.1128/jb.169.2.495-499.1987
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of glutamate in the respiratory metabolism of Bradyrhizobium japonicum bacteroids

Abstract: pestle, with 0.15 M sodium phosphate buffer, pH 7.5, added in 2-ml portions to a final volume of 2 ml of buffer per g of nodules. The homogenate was filtered through two Miracloth disks in a 50-ml syringe into a 30-ml centrifuge tube. The tube was capped tightly and centrifuged at 6,000 x g for 10 min. The tube was opened in the glove box, the supernatant was discarded, and the pellet was washed twice by pipetting 1 ml of the buffer over it. The pellet was resuspended, and the mixture was again filtered throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0
1

Year Published

1989
1989
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 29 publications
11
50
0
1
Order By: Relevance
“…The I4CO2 evolved is also an underestimation, because the dissolved C 0 2 is not accounted for. The 14C02 release is, however, proportional to the total C 0 2 respired and shows a linear increase after a lag period (Salminen & Streeter, 1987).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The I4CO2 evolved is also an underestimation, because the dissolved C 0 2 is not accounted for. The 14C02 release is, however, proportional to the total C 0 2 respired and shows a linear increase after a lag period (Salminen & Streeter, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that, when Bradyrhizobium japonicum bacteroids were isolated anaerobically and supplied with [ U-14C]succinate or [U-14C]malate under microaerobic conditions, 20 to 40% of the label taken up was converted to glutamate (Salminen & Streeter, 1987). When only the 14C remaining in bacteroids is considered ( 4C02 subtracted), glutamate accounted for 75 % of the radioactivity recovered.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations